Currency Mismatches and Vulnerability to Exchange Rate Shocks : Nonfinancial Firms in Colombia - Barajas, Adolfo; Camilo Medellin, Juan.; Restrepo, Sergio; Steiner, Roberto (Washington, D.C. : International Monetary Fund, 2017)
After building up foreign currency denominated (FC) liabilities over several years, Colombian firms might be vulnerable to a shift in external conditions. We undertake three empirical exercises to better understand these vulnerabilities. First, we identify the determinants of FC borrowing. Second, we investigate the implications for real activity, finding a balance sheet effect that transmits exchange rate fluctuations to investment and is asymmetric, much stronger for depreciations than for appreciations. Finally, we find that foreign exchange derivatives are not used solely for hedging, due in part to monetary authority intervention to smooth exchange rate volatility. However, a full explanation remains open for future research.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet